The Improvement on the Boundedness and Norm of a Class of Integral Operators on Lp Space. (6th April 2015) - Zhou, Lifang; Lu, Jin
Abstract : We prove the condition "c is neither0 nor a negative integer" can be dropped on the boundedness of a class of integral operatorsS a, b, c onL p space, which improves the result by Krues and Zhu. Besides, the exact norm ofS a, b, c onL p space is also obtained under the assumptionc = n + 1 + a + b .